Associations of day of week and time of day of ICU admission with hospital mortality in Malawi. (October 2020) - Prin, Meghan; Ji, Ruoyu; Kadyaudzu, Clement; Li, Guohua; Charles, Anthony
This prospective cohort study evaluated the associations of day and time of admission to the Intensive Care Unit (ICU) with hospital mortality at a referral hospital in Malawi, a low-income country in sub-Saharan Africa. Patients admitted to the ICU during the day (08:00–16:00) were compared to those admitted at night (16:01–07:59); patients admitted on weekdays (Monday–Friday) were compared to admissions on weekends/holidays. The primary outcome was hospital mortality. Most patients were admitted during daytime (56%) and on weekdays (72%). There was no difference in mortality between night and day admissions (58% vs. 56%, P = 0.8828; hazard ratio [HR] = 1.09, 95% confidence interval [CI = 0.82–1.44, P = 0.5614) or weekend/holiday versus weekday admissions (56% vs. 57%, P = 0.9011; HR = 0.87, 95% CI = 0.62–1.21, P = 0.4133). No interaction between time and day was found. These results may be affected by high overall hospital mortality.